Literary Taste Between Al-Qadi Al-Jurjani and Abdul-Qahir Al-Jurjani: A Comparative Study - Al-Fayfī, Mūsā Hādī (Journal of Arabic Language Sciences and Literature, 2025)
Literary taste in the sources of rhetorical and critical heritage is considered one of the standards of literary criticism and a tool for receiving and judging literary discourse. The uses of literary taste varied in these sources, and scholars' positions differed in both application and theory, which the researcher seeks to clarify in this study through a comparison between what was proposed regarding literary taste by: Judge Ali bin Abdul Aziz Al-Jurjani in his book (Mediation Between Al-Mutanabbi and His Opponents), and Imam Abdul-Qahir bin Abdul-Rahman Al-Jurjani in his two books (Secrets of Rhetoric and Evidence of Inimitability). The researcher will rely on the comparative approach to identify similarities and differences, describing their manifestations, monitoring their causes, and their possible implications. The researcher found that literary taste represents a critical methodology in reading and judging literary texts for both authors under comparison. Because they acknowledge the variation in recipients' tastes, they sought to establish conditions for taste that is considered valid in critical judgment, most of which revolve around the critic's qualifications. Abdul-Qahir was distinguished by his call for the necessity of justifying critical judgments with taste-based references and his commitment to applying this in most of his proposals, unlike the approach of  Al-Qadi Al-Jurjani, which was based on not justifying taste judgments in much of his work. Thanks to Abdul-Qahir's approach based on justifying taste judgments, the study of literary discourse moved from subjectivity to objectivity, and from impressionism to scientific methodology.
Keywords: Literary taste; Critical taste; Taste judgments; Taste justification